EFFICIENCY OF AN INDIVIDUAL REHABILITATION PROGRAM FOR PATIENTS WITH RHEUMATOID ARTHRITIS - E V Orlova; D E Karateev; V N Amirdjanova (Научно-практическая ревматология)
Objective. To evaluate the efficacy of an individual rehabilitation program (IRP) for patients with rheumatoid arthritis (RA), by using hardware methods (COBS platform, En-Tree M motion analysis) and the quality-of-life index RAPID3. Subjects and methods. The study enrolled 46 patients with RA. Of them, 35 patients underwent drug therapy and IRP (40-min exercise therapy for large joints under the supervision of a trainer, 40-min occupational therapy, local air cryotherapy (-60°C) for hand, knee, or ankle joints for 15 min, 10 sessions), 11 patients received only drug therapy (a control group). The COBS platform was used to measure a symmetry index (SI) and load distribution in different modes. The authors determined the average power of knee extension and ankle flexion by the En-Tree M system, hand grip strength, and DAS28 and RAPID3 scores. Results. Thirty-two patients finished IRP. After IRP, the grip strength of a more affected hand was enhanced by 29% (p < 0.05). RAPID3 scores decreased by 3.25±0.43 (27%) (p < 0.05). The reduction in DAS28 scores was not statistically significant. In the patients with knee arthritis, the pressure from habitual standing on the COBS platform of an extremity with a more affected joint increased by 11% (p < 0.05) and SI rose by 13% (p < 0.05). The rising-from-sitting load on the limb with a more affected joint was elevated by 13% (p < 0.05), SI increased by 25% (p < 0.05). The average extension power for a weaker knee was increased by 88% (p < 0.01). In the patients with ankle arthritis, the habitual-standing pressure on the COBS platform of an extremity with a more affected joint was enhanced by 14% (p < 0.05), SI increased by 18% (p < 0.05). The toes-rising load on the limb with a more affected joint increased by 12% (p < 0.05), SI rose by 20% (p < 0.05). The flexion power of a weaker ankle joint was increased by 68% (p < 0.01). There were no statistically significant changes in most parameters in the control group. Conclusion. The COBS platform and En-Tree M motion analysis allow one to estimate the functional status of each joint group of the lower limbs. IRP improves functional ability and motion activity (hand grip strength, power, symmetry of movements, load distribution) and quality of life in RA patients immediately after its completion.